RAV-1 insertional mutagenesis: disruption of the c-myb locus and development of avian B-cell lymphomas. - Pizer, E (1989)
Infection of young chickens with RAV-1, a subgroup A isolate of avian leukosis virus, results in the development of lymphoid leukosis, a B-cell lymphoma characterized by provirus insertion into the c-myc locus. We report here that when 12- to 13-day-old embryos rather than 1-day-old chickens were infected with RAV-1, a novel B-cell lymphoma developed in which proviral insertions had activated expression of the c-myb gene. These tumors expressed elevated levels of a 4.5-kilobase myb-containing mRNA transcript that contained c-myb sequences not found in v-myb. The c-myc locus in these tumors appeared normal. The biological properties of the activated myb lymphoma were distinct from those of lymphoid leukosis. Metastatic disease developed within 7 weeks of infection. Distinct intermediate pathogenic stages with preneoplastic and primary neoplastic lesions were not detected. Although bursal tissues appeared to be nonmalignant on gross examination, Southern analyses of bursal DNA revealed the presence of tumor with the same clonal origin as abdominal lymphoma masses. The dependence on embryonic infection for development of activated myb lymphoma suggests that the target cells in which c-myb is activated are found only in embryos and are distinct from those cells that give rise to lymphoid leukosis.